The Phlorizin-Degrading Bacillus licheniformis XNRB-3 Mediates Soil Microorganisms to Alleviate Apple Replant Disease - Duan, Yanan; Zhao, Lei; Jiang, Weitao; Chen, Ran; Zhang, Rong; Chen, Xuesen; Yin, Chengmiao; Mao, Zhiquan (Frontiers in Microbiology, 2022)
In this study, an endophytic phlorizin-degrading Bacillus licheniformis XNRB-3 was isolated from the root tissue of healthy apple trees, and its control effect on apple replant disease (ARD) and how it alleviates the pathogen pressure via changes in soil microbiomes were studied. The addition of strain XNRB-3 in Fusarium infested soils significantly reduced the number of pathogens in the soil, thus resulting in a lower disease incidence, and the relative control effect on Fusarium oxysporum reached the highest of 66.11%. The fermentation broth can also protect the roots of the plants from Fusarium oxysporum, Fusarium moniliforme, Fusarium proliferatum, and Fusarium solani infection. These antagonistic effects were further validated using an in vitro assay in which the pathogen control was related to growth and spore germination inhibition via directly secreted antimicrobial substances and indirectly affecting the growth of pathogens. The secreted antimicrobial substances were identified using gas chromatography-mass spectrometry (GC-MS) technology. Among them, alpha-bisabolol and 2,4-di-tert-butylphenol had significant inhibitory effects on many planted pathogenic fungi. Butanedioic acid, monomethyl ester, and dibutyl phthalate promoted root development of Arabidopsis plants. Strain XNRB-3 has multifarious plant growth promoting traits and antagonistic potential. In pot and field experiments, the addition of strain XNRB-3 significantly promoted the growth of plants, and the activity of enzymes related to disease resistance (superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT)) was also significantly enhanced. It also reduced the abundance of four species of Fusarium and the content of phenolic acids in the rhizosphere soil, improved soil microbial community structure and nutritional conditions, and increased soil microbial diversity and activity, as well as the soil enzyme activity. The above results indicated that B. licheniformis XNRB-3 could be developed into a promising biocontrol and plant-growth-promoting agent.